A metal oxide catalyst based on Prussian blue sodium ion battery positive electrode material, preparation method and application

By using the metal oxide catalyst Fe3O4@biochar prepared from waste Prussian blue sodium ion batteries and crop straws to activate sodium persulfate oxidizer, the problems of decommissioned batteries and dye wastewater treatment were solved, and efficient degradation and recycling were achieved.

CN118988317BActive Publication Date: 2025-03-07SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411433862.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-07
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with retired Prussian blue sodium ion batteries and difficult-to-degrade dye wastewater, resulting in environmental pollution and waste of resources.

Method used

The metal oxide catalyst Fe3O4@biochar is prepared by using waste Prussian blue sodium ion batteries and waste crop straws, and used to activate sodium persulfate oxidizer to achieve degradation of dye wastewater.

Benefits of technology

The "use waste to control waste" has been achieved, effectively reducing the cost of pollution treatment, promoting the development of the circular economy, and multiple recycling has been achieved through the magnetic properties of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118988317B_ABST
    Figure CN118988317B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of waste power battery recycling, specifically a metal oxide catalyst based on Prussian blue sodium ion battery positive electrode material, preparation method and application; the preparation method of the metal oxide catalyst of the present invention comprises: disassembling the battery to recover the positive electrode material; removing impurities from the positive electrode material; biomass modification; using ball milling to compound the positive electrode material and the modified biomass together and finally sintering at high temperature to form a metal oxide@biochar composite material. The present invention degrades dye wastewater by activating persulfate with prepared Fe3O4@biochar. The present invention not only has good treatment effect and no secondary pollution, but also can use the magnetism of Fe3O4 to quickly recover the catalyst in the water, further improving the utilization rate of resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste power battery recycling, and in particular to a metal oxide catalyst prepared based on a Prussian blue sodium ion battery positive electrode material, a preparation method and an application thereof. Background Art

[0002] As the demand for batteries continues to increase, a large number of retired sodium-ion batteries will be produced in the next few years. For Prussian blue (Na2FeFe(CN)6) sodium-ion batteries, if they are not properly handled, retired sodium batteries will cause serious harm to the environment. The positive electrode reuse of battery materials has alleviated the dilemma of battery recycling to a certain extent, realizing a closed loop from production to recycling, which is closer to the policy requirements of low-carbon and environmental protection.

[0003] On the other hand, dye wastewater has certain toxicity and carcinogenicity. At the same time, as a type of wastewater with high chromaticity, high content of pollutants and difficulty in degradation, it is not easy to be degraded by biological methods. The advanced oxidation technology based on persulfate PDS is an effective method for treating difficult-to-degrade organic wastewater. This method uses different methods to activate monosulfate and peroxydisulfate to produce SO4 with high redox potential and strong oxidizing ability. 2- , which can effectively destroy the structure of organic pollutants. With the continuous in-depth research on materials, it is found that transition metals have good catalytic properties. In the system of catalytic materials activating persulfate, the catalyst can be divided into homogeneous and heterogeneous according to the phase state. Due to the dual advantages of adsorption and catalysis, iron-based biochar (Fe-biochar) has also been widely used as a heterogeneous catalyst in the field of activating persulfate to degrade organic pollutants. Summary of the invention

[0004] Based on the above-mentioned prior art, the purpose of the present invention is to provide a metal oxide catalyst based on Prussian blue sodium ion battery positive electrode material, a preparation method and an application; the present invention prepares a metal oxide catalyst based on discarded Prussian blue sodium ion batteries and discarded crop straw and then uses it to treat dye wastewater, thereby realizing "waste treatment with waste", which can effectively reduce pollution treatment costs and promote the development of a circular economy.

[0005] The technical solution of the present invention is specifically described as follows.

[0006] The present invention provides a method for preparing a metal oxide catalyst based on a Prussian blue sodium ion battery positive electrode material, comprising the following steps:

[0007] Step 1: discharging, disassembling and sorting the discarded Prussian blue sodium ion battery to obtain a positive electrode sheet; placing the positive electrode sheet in deionized water for ultrasonic vibration cleaning until the positive electrode material and the current collector are completely separated; filtering and drying, grinding and pouring into a 100-mesh stainless steel mesh sieve, and sieving to obtain a positive electrode powder rich in Prussian blue;

[0008] Step 2: stirring and dissolving the positive electrode powder obtained in step 1 in a polar organic solvent for a period of time, and then filtering, washing and drying the obtained solid sample to obtain the positive electrode powder without the binder;

[0009] Step 3: After drying and grinding the straw, put it into nitric acid for full soaking and stirring, and then filter, wash and dry it in sequence to obtain modified biomass;

[0010] Step 4: mixing and ball-milling the positive electrode powder from which the binder has been removed and the modified biomass to obtain a mixed material;

[0011] Step 5: heat-treating the mixture under an inert atmosphere to obtain the metal oxide catalyst Fe3O4@biochar.

[0012] Preferably, in step 1, the ultrasonication time is 4-6 hours, and the drying is carried out by vacuum drying or hot air drying at a drying temperature of 60-70°C.

[0013] Preferably, in step 2, the polar organic solvent is N-methylpyrrolidone, the solid-liquid ratio of the positive electrode powder to N-methylpyrrolidone is 15:1~30:1g / L, the stirring speed is 200-300r / min, and the stirring time is 2-5h; washing with water 3-4 times, drying by vacuum drying or hot air drying, and the drying temperature is 60-70°C; the reason for removing the binder is that the binder will cause the positive electrode material to agglomerate and exist in a block form. Failure to remove it will affect the performance of the finally prepared metal oxide catalyst.

[0014] Preferably, in step three, the nitric acid concentration is 2-4 mol / L, the stirring speed is 200-300 r / min, and the stirring time is 8-12 h; washing with water 3-4 times, drying by vacuum drying or hot air drying, and the drying temperature is 50-60°C; the purpose of nitric acid treatment is to increase the specific surface area of ​​the prepared biochar.

[0015] Preferably, in step 4, the mass ratio of the positive electrode powder from which the binder is removed to the modified biomass is 1:1-1:3, the ball milling speed is 300-500 r / min, and the ball milling time is 3-5h.

[0016] Preferably, in step 5, the inert atmosphere is nitrogen, and the heat treatment procedure is as follows: heating from room temperature to 550°C-650°C at a heating rate of 8-15°C / min, keeping the temperature for 0.5-5h, and then cooling naturally to room temperature. Further preferably, the heat treatment temperature is 550-600°C, and the holding time is 1-3h.

[0017] The present invention also provides a metal oxide catalyst prepared by the above preparation method.

[0018] Furthermore, the present invention provides the use of the above metal oxide catalyst in treating dye wastewater. The metal oxide catalyst Fe3O4@biochar is used as an activator to activate the sodium persulfate Na2S2O8 oxidant to achieve the degradation of the dye wastewater.

[0019] Preferably, the dye wastewater is Rhodamine B wastewater; the dye wastewater is Rhodamine B wastewater, the concentration of Rhodamine B wastewater is between 10-100 mg / mL, the mass ratio of Fe3O4@biochar and sodium persulfate Na2S2O8 is 4:3~4:5, and the degradation time is 30-90 min.

[0020] Compared with the prior art, the advantages of the present invention are:

[0021] (1) The battery powder of the present invention is mainly derived from waste Prussian blue sodium ion batteries, and the biochar is derived from waste crop straw, which has a wide source, low cost and price friendliness; the Fe3O4@biochar prepared by the present invention is used to treat the organic dye Rhodamine B, and the wastewater after the organic dye is treated by the present invention can also be quickly recovered for recycling through the magnetism of Fe3O4, which further improves the utilization rate of resources.

[0022] (2) The present invention uses modified biomass as a carrier, and the two are compounded together by ball milling, and finally sintered at high temperature. On the one hand, the agglomeration phenomenon of Fe3O4 is solved; on the other hand, the adsorption effect of pollutants is increased by the large pore size characteristics of modified biochar; Fe3O4 not only has a highly efficient catalytic effect on persulfate PDS, but can also be quickly recovered and recycled through its own magnetism.

[0023] (3) The present invention provides a method for recycling and reusing waste Prussian blue sodium ion batteries and a method for recycling waste straw, which has no secondary pollution, reduces the cost of material recycling and protects the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a transmission electron microscopy image of the Fe3O4@biochar synthesized in Example 1.

[0025] Figure 2This is the X-ray diffraction pattern of Fe3O4@biochar synthesized in Example 1, Example 2 and Comparative Example 1.

[0026] Figure 3 : (a) is a scanning electron microscope image of the positive electrode powder in Comparative Example 2 that was not immersed in N-methylpyrrolidone solution; (b) is a scanning electron microscope image of the positive electrode powder in Example 1 after being immersed in N-methylpyrrolidone solution.

[0027] Figure 4 : (a) is a scanning electron microscope image of the modified biochar obtained after treatment of the modified biomass carbon; (b) is a scanning electron microscope image of the unmodified biochar obtained after treatment of the unmodified biomass carbon in Comparative Example 3.

[0028] Figure 5 This is a graphical representation of the degradation results of Rhodamine B wastewater when Na2S2O8 was activated using different dosages of Fe3O4@biochar.

[0029] Figure 6 This is a graphical representation of the degradation results of Rhodamine B wastewater at different Na2S2O8 dosages.

[0030] Figure 7 This is the magnetic test diagram of Fe3O4@biochar synthesized in Example 1.

[0031] Figure 8 This is a test chart of the recycling and repeated application of Fe3O4@biochar synthesized in Example 1, where: in the ordinate, C0 is the initial rhodamine B concentration, mg·L -1 ; C is the concentration of rhodamine B after degradation, mg·L -1 . DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below in conjunction with the embodiments and drawings.

[0033] Example 1

[0034] Step 1: Discharge the recovered Prussian blue sodium ion battery, disassemble and sort the recovered positive electrode sheet; put the positive electrode sheet into a beaker, add an appropriate amount of deionized water, and then put it into an ultrasonic cleaning machine for 6 hours until the positive electrode powder is separated from the current collector. Filter the filtrate, put the filter residue into a drying oven at 60°C and dry it for 5 hours, filter and dry it, grind it and pour it into a 100-mesh stainless steel mesh sieve, and sieve it to obtain the positive electrode powder rich in Prussian blue.

[0035] Step 2: Put the positive electrode powder into a sample bottle, add N-methylpyrrolidone solution, stir at 200r / min for 4 hours, filter the filtrate, wash the solid product with deionized water 3 times, and dry at 60°C for 5 hours to obtain the positive electrode powder with the binder impurities removed; the solid-liquid ratio of the positive electrode powder to the N-methylpyrrolidone solution is 20g / L.

[0036] Step three, wash, dry, grind and soak the recovered straw in 2-4 mol / L nitric acid, stir at 200 r / min for 8 hours, filter the filtrate, wash the residue with deionized water three times until the washing liquid is neutral, and vacuum dry to obtain modified biomass.

[0037] Step 4: ball-mill the positive electrode powder obtained in step 2 and step 3 and the modified biomass in a mass ratio of 1:1 to uniformly mix the materials, and then perform carbonization treatment to obtain Fe3O4@biochar catalyst.

[0038] The ball milling speed is 300r / min, and the ball milling time is 4h.

[0039] Specifically, the carbonization treatment is as follows: under nitrogen protection, the mixed material is placed in a box-type vacuum atmosphere furnace, the temperature is raised from room temperature to 600°C at a rate of 10°C / min, and after reaching the target temperature, the temperature is kept for 1.5 hours, and then naturally cooled to room temperature to obtain a Fe3O4@biochar catalyst sample. The TEM image and XRD image of the Fe3O4@biochar catalyst sample obtained in this embodiment are shown in Figure 1. Figure 1 , Figure 2 shown.

[0040] Example 2

[0041] A method for preparing a metal oxide catalyst based on Prussian blue sodium ion battery positive electrode material is the same as Example 1 except that the temperature of the box-type vacuum atmosphere furnace in step 4 is set to 550°C.

[0042] The XRD pattern of the Fe3O4@biochar catalyst sample obtained in this example is shown in Figure 2 shown.

[0043] Comparative Example 1

[0044] A method for preparing a metal oxide catalyst based on Prussian blue sodium ion battery positive electrode material is the same as Example 1 except that the temperature of the box-type vacuum atmosphere furnace in step 4 is set to 500°C.

[0045] The XRD pattern of the Fe3O4@biochar catalyst sample obtained in this comparative example is shown in Figure 2 shown.

[0046] Figure 2 In the figure, the Fe3O4@biochar synthesized at 500℃ has no obvious biochar peak, while those synthesized at 550℃ and 600℃ have obvious biochar peaks and Fe3O4 peaks.

[0047] Comparative Example 2

[0048] The same as Example 1, except that step 2 is omitted, and the electron microscope image of the obtained positive electrode powder is as follows: Figure 3 As shown in (a), and Figure 3 The scanning electron microscope image of the positive electrode powder after immersion in N-methylpyrrolidone solution in Example 1 shown in (b) is compared. The results show that the removal of the binder is necessary. The presence of the binder will cause the positive electrode material to form agglomerates. Removing the binder can disperse the material to form small particles.

[0049] Comparative Example 3

[0050] The recovered straw was washed, dried, and ground, and then directly subjected to the carbonization treatment in Example 1 to obtain an unmodified biochar sample.

[0051] Electron microscopy images of unmodified biochar samples are shown in Figure 2. Figure 4 As shown in (b), and Figure 4 The scanning electron microscope images of the modified biochar obtained by direct carbonization treatment of the modified biomass prepared in Example 1 shown in (a) are compared. The results show that the nitric acid acidification treatment of the straw can increase the pore size of the sample, and the modified biomass has better pore size characteristics after heat treatment, and has better positive electrode powder accommodation and pollutant adsorption.

[0052] Application performance testing

[0053] Purchase Rhodamine B and Na2S2O8 on the market.

[0054] 50 mg / L of Rhodamine B wastewater was prepared as simulated wastewater, and the Fe3O4@biochar catalyst prepared in Example 1 and Na2S2O8 as an active oxidant were used to treat the Rhodamine B wastewater. The reaction time was 1 hour, and samples were taken every 15 minutes to measure and analyze the degradation degree of Rhodamine B using an L5 ultraviolet spectrophotometer. The optimal amount of Fe3O4@biochar and the effect of the addition amount of the active oxidant Na2S2O8 on the experiment were analyzed, and a single biochar (carbonization after straw nitric acid treatment, the process parameters and conditions were the same as in Example 1) was prepared for comparison with the present invention. The results are shown in Tables 1-3. Figure 5-Figure 6 .

[0055] All three groups of experiments were conducted with 100 mL, 50 mg / L Rhodamine B wastewater as the treatment object.

[0056] Table 1 Effect of Fe3O4@biochar addition on the experiment

[0057]

[0058] Table 2 Effect of the addition amount of Na2S2O8 on the experiment

[0059]

[0060] Table 3 Effect of single biochar on RhB degradation

[0061]

[0062] As can be seen from Table 1 and Table 2, the catalyst prepared by the present invention has a good degradation effect on Rhodamine B wastewater. The prepared Fe3O4@biochar can achieve a degradation effect of more than 95% at the optimal dosage, which almost completely treats the Rhodamine B in the solution. And after the end, the magnetism of Fe3O4 can be used to quickly recover the Fe3O4@biochar in the wastewater to achieve multiple recycling. For a single biochar, its catalytic efficiency can only reach 64%, which is much less than Fe3O4@biochar. The Fe3O4@biochar prepared by the present invention not only provides a new recycling method for waste Prussian blue sodium ion batteries, but also its degradation effect and adsorption effect are much higher than the use of a single biochar. And it is also a new treatment method for dyes that are difficult to degrade.

[0063] The catalyst prepared in the embodiment of the present invention has magnetism. After treating the wastewater, the catalyst can be recovered from the water by magnetism. Figure 7 As shown, Figure 8 This is the experimental result of the catalyst being repeatedly recovered from wastewater five times and used again for water treatment. The figure shows that the pollutant concentrations dropped rapidly in the five treatments and the final concentration was very low, proving that the catalyst has not failed after multiple uses.

[0064] The above describes the basic principle and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above examples, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected, and the scope of the present invention to be protected is defined by the attached claims and their equivalents.

Claims

1. An application of a metal oxide catalyst based on a Prussian blue sodium ion battery cathode material in treating dye wastewater, characterized in that: The metal oxide catalyst is Fe3O4@biochar, which uses the metal oxide catalyst Fe3O4@biochar as an activator to activate the sodium persulfate Na2S2O8 oxidant to achieve the degradation of dye wastewater; wherein: the preparation method of the metal oxide catalyst includes the following steps: Step 1: discharging, disassembling and sorting the discarded Prussian blue sodium ion battery to obtain a positive electrode sheet; placing the positive electrode sheet in deionized water for ultrasonic vibration cleaning until the positive electrode material and the current collector are completely separated; filtering and drying, grinding and pouring into a 100-mesh stainless steel mesh sieve, and sieving to obtain a positive electrode powder rich in Prussian blue; Step 2: stirring and dissolving the positive electrode powder obtained in step 1 in a polar organic solvent for a period of time, and then filtering, washing and drying the obtained solid sample to obtain the positive electrode powder from which the binder is removed; Step 3: After drying and grinding the straw, put it into nitric acid for full soaking and stirring, and then filter, wash and dry it in sequence to obtain modified biomass; Step 4: mixing and ball-milling the positive electrode powder from which the binder has been removed and the modified biomass to obtain a mixed material; Step 5. Heat treat the mixture under an inert atmosphere to obtain the metal oxide catalyst Fe3O4@biochar; the inert atmosphere is nitrogen, and the heat treatment procedure is as follows: heat up from room temperature to 550°C-650°C at a heating rate of 8-15°C / min, keep warm for 0.5h-5h, and then cool naturally to room temperature.

2. The use according to claim 1, characterized in that: In step 1, the ultrasonication time is 4-6 hours, and the drying is carried out by vacuum drying or hot air drying at a drying temperature of 60-70°C.

3. The use according to claim 1, characterized in that: In step 2, the polar organic solvent is N-methylpyrrolidone, the solid-liquid ratio of the positive electrode powder to N-methylpyrrolidone is 15:1~30:1g / L, the stirring speed is 200-300r / min, and the stirring time is 2-5h; washing with water 3-4 times, drying by vacuum drying or hot air drying, and the drying temperature is 60-70°C.

4. The use according to claim 1, characterized in that: In step 3, the concentration of nitric acid is 2-4 mol / L, the stirring speed is 200-300 r / min, and the stirring time is 8-12 h; washing with water 3-4 times, drying by vacuum drying or hot air drying, and the drying temperature is 50-60°C.

5. The use according to claim 1, characterized in that: In step 4, the mass ratio of the positive electrode powder without the binder and the modified biomass is 1:1-1:3, the ball milling speed is 300-500 r / min, and the ball milling time is 3-5h.

6. The use according to claim 1, characterized in that: The dye wastewater is Rhodamine B wastewater, the concentration of Rhodamine B wastewater is between 10-100 mg / mL, the mass ratio of Fe3O4@biochar and sodium persulfate Na2S2O8 is 4:3~4:5, and the degradation time is 30-90 min.

Citation Information

Patent Citations

  • Recycling method and application of waste sodium-ion battery positive electrode material

    CN118231824A